Development Of National Payment Hateway (NPG) for Efficient Payment System In Indonesia - Suprapto, .; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2015)
Abstract - Payment systems industry in Indonesia plays an important role in Indonesian economy. It regulates how to move funds from one place to another, whether for transfer, payment or purchase. Along with development of Indonesian economy and free trade in ASEAN, many parties are involved in the Indonesia payment systems industry, either domestic or international party. Each party has its own model, which leads to inefficiency and lack of integration of payment systems in Indonesia. Seeing this, Bank Indonesia as a regulator in the payment system in Indonesia deems it necessary to make the payment system infrastructure in Indonesia is more efficient and integrated also to perform control functions and provide convenience for the Indonesian people. This final project will focus on how Bank Indonesia strategy to make payment systems industry become more efficient as well as determines the alternative design and implement the National Payment Gateway (NPG) as a solution. Having regard to the condition of the industry as well as players who have been involved at this time. Based on the analysis, in order to implement the National Payment Gateway (NPG) is required an integration system with control of Bank Indonesia and supported by a special regulation for the policy so that the whole industry will support to participate operational activities. The implementation stages will takes an integrated roadmap to connect all payment system instruments such as debit, credit, cash and e-money for making synergize within National Payment Gateway (NPG) system.Ã‚Â Keywords: Payment Systems, National Payment Gateway (NPG), Bank Indonesia Strategy, Efficient and Integration, Alternative design solutions.